Congenital Anterior Urethral Diverticulum: A Case Report - Dangol, Ellina; Thapa, Bijay; Thapa Basnet, Anupama (Nepalese Medical Journal, 2024)
Congenital anomalies of lower urinary tract are most common anomalies found in children, but congenital anterior urethral diverticulum is a very rare cause. Here we present 11 month old male child presented with soft cystic swelling in the ventral side of the penile shaft and underwent open diverticulectomy.